Vinyl resin composition, and cured product
A vinyl resin composition with crystalline vinyl resin and layered clay minerals addresses the limitations of existing compositions by enhancing thermal conductivity, dielectric properties, and moldability, suitable for electronic materials and circuit boards.
Patent Information
- Application Number
- JP2023107268
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-01-17
AI Technical Summary
Existing vinyl resin compositions for electronic materials face challenges in achieving high thermal conductivity, low dielectric constant, low dielectric loss tangent, and flame retardancy while maintaining moldability and solvent solubility, due to limitations in increasing the content of inorganic fillers and the use of aromatic diamine compounds, which hinder fluidity and electrical insulation.
A vinyl resin composition containing a crystalline vinyl resin with a melting point of 90 to 200°C and layered clay minerals, such as talc, in the range of 1 to 20 parts by weight, along with optional inorganic fillers, to enhance thermal conductivity and improve moldability and solvent solubility.
The composition achieves excellent heat resistance, thermal decomposition stability, low dielectric constant, low dielectric loss tangent, and flame retardancy, suitable for sealing electrical and electronic parts and circuit board materials, with thermal conductivity exceeding 8 W/m·K.
Smart Images

Figure 2025006458000026 
Figure 2025006458000027 
Figure 2025006458000028
Abstract
Description
[Technical field]
[0001] The present invention relates to vinyl resin compositions which are useful as insulating materials for electric and electronic materials such as semiconductor encapsulation, laminates, and heat dissipation substrates, and to cured resin products obtained by curing the vinyl resin compositions, which have excellent solvent solubility, moldability, heat resistance, thermal decomposition stability, thermal conductivity, low dielectric constant, low dielectric tangent, and flame retardancy. [Background technology]
[0002] As communication speeds and volumes increase, research is being actively conducted into high-speed communication technologies to improve signal transmission speeds for printed circuit boards, sealing materials, casting materials, etc. used in communication devices. Electronic materials for such applications require materials that can reduce dielectric loss, and for printed circuit board applications, curable resins that can be multi-layered are also required.
[0003] On the other hand, electronic computing components that process such large amounts of data generate a lot of heat, and heat accumulation can cause problems such as a decrease in the processing speed of the electronic computing components, so various methods are known for appropriately cooling printed circuit boards using heat sinks, etc., such as incorporating heat transfer members such as copper coins and copper inlays (Patent Document 1) or using special shapes for the fillers to be mixed (Patent Document 2).However, such methods are undesirable as they lead to increased weight and larger equipment.
[0004] In addition, in the case of an encapsulant composition, a method of removing heat from electronic computing components by examining the type and amount of various fillers has been adopted as a method of increasing the thermal conductivity, and for example, attempts have been made to include inorganic fillers such as crystalline silica, silicon nitride, aluminum nitride, and spherical alumina powder, which have high thermal conductivity (Patent Documents 3 and 4). However, as the content of the inorganic filler is increased, the viscosity during molding increases and the fluidity decreases, causing a problem of impaired moldability. Therefore, there is a limit to the method of simply increasing the content of the inorganic filler.
[0005] In light of the above background, a method for improving the thermal conductivity of a composition by increasing the thermal conductivity of the matrix resin itself has also been studied. For example, liquid crystalline epoxy resins having rigid mesogen groups and epoxy resin compositions using the same have been proposed (Patent Documents 5 and 6). However, aromatic diamine compounds are used as curing agents for these epoxy resin compositions, and there is a limit to increasing the filling rate of inorganic fillers, and there are also problems with electrical insulation. In addition, when aromatic diamine compounds are used, although the liquid crystallinity of the cured product can be confirmed, the crystallinity of the cured product is low, and it is not sufficient in terms of high thermal conductivity, low thermal expansion, low moisture absorption, etc. Furthermore, in order to express liquid crystallinity, it is necessary to apply a strong magnetic field to orient the molecules, and there are significant restrictions in terms of equipment for widespread industrial use. In addition, in a blended system with an inorganic filler, the thermal conductivity of the inorganic filler is overwhelmingly larger than that of the matrix resin, and even if the thermal conductivity of the matrix resin itself is increased, it does not contribute significantly to improving the thermal conductivity of the composite material, and existing resins have not been able to achieve a sufficient effect of improving thermal conductivity.
[0006] Layered clay minerals such as talc are generally used to improve fluidity and reduce the linear expansion coefficient. Although a combination of layered clay minerals and inorganic fillers with high thermal conductivity has been proposed, this is due to the contact between inorganic materials, and does not affect the matrix resin itself (Patent Document 7).
[0007] Patent Document 8 discloses a tetrafunctional or higher vinyl resin having a biphenyl skeleton as a multifunctional vinyl resin that combines high thermal conductivity and low dielectric tangent. However, there is no description of the solvent solubility of the multifunctional vinyl resin and the polyhydric hydroxyl resin that is its raw material, and there is no mention of the effect of impurities such as residual polar groups on thermal conductivity. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2009-170493 A [Patent Document 2] International Publication No. WO2013 / 100172 [Patent Document 3] Japanese Patent Application Publication No. 11-147936 [Patent Document 4] JP 2002-309067 A [Patent Document 5] Japanese Patent Application Publication No. 11-323162 [Patent Document 6] Japanese Patent Application Publication No. 9-118673 [Patent Document 7] International Publication No. WO2013 / 100174 [Patent Document 8] International Publication No. WO2021 / 200414 Summary of the Invention [Problem to be solved by the invention]
[0009] An object of the present invention is to provide a vinyl resin composition which overcomes the above-mentioned problems, gives a cured product which is excellent in solvent solubility and moldability, and which is useful for sealing electric and electronic parts, as a circuit board material, etc., and which gives a cured product which is excellent in heat resistance, thermal decomposition stability, thermal conductivity, low dielectric constant, low dielectric tangent and flame retardancy, and to provide a cured product thereof. [Means for solving the problem]
[0010] Through extensive research, the present inventors have discovered that a thermally conductive vinyl resin composition containing a crystalline vinyl resin having a melting point in a specific range and a layered clay mineral is expected to solve the above-mentioned problems, and that the cured product thereof exhibits effects such as thermal conductivity, low dielectric constant, and low dielectric tangent.
[0011] That is, the present invention is a vinyl resin composition comprising a vinyl resin and an additive, wherein the additive is a layered clay mineral, the vinyl resin composition contains 1 to 20 parts by weight of the layered clay mineral per 100 parts by weight of the resin component, and the melting point of the vinyl resin is 90 to 200°C.
[0012] Preferably, the above-mentioned additive is talc.
[0013] The vinyl resin described above preferably has a vinyl equivalent of 150 to 1000 g / eq, a hydroxyl equivalent of 5000 g / eq or more, and a total chlorine content of 2000 ppm or less.
[0014] Furthermore, vinyl resins represented by at least one of the following general formulas (1) to (3) are more preferred. [ka] In formula (1), R 1 ~R 6 each independently represents a hydrogen atom or a monovalent hydrocarbon group having 1 to 6 carbon atoms. [ka] In formula (2), A is independently a single bond, an oxygen atom, a sulfur atom, or -SO 2 It represents -, -CO-, or a divalent hydrocarbon group having 1 to 6 carbon atoms, X is independently a benzene ring, a naphthalene ring, or a biphenyl ring, and n is a number from 0 to 20. [ka] In formula (3), Y is independently a single bond, an oxygen atom, a sulfur atom, or -SO 2 -, -CO-, -COO-, -CONH-, -CH 2 - or -C(CH 3 ) 2 B is independently a benzonitrile structure or -(CH 2 ) q -, p represents a number from 0 to 15, and q represents a number from 3 to 10.
[0015] Furthermore, the vinyl resin composition of the present invention may contain an inorganic filler other than layered clay minerals, and the content thereof is preferably 20 to 90 wt %.
[0016] The vinyl resin composition of the present invention is suitable for use in providing a cured product with high thermal conductivity.
[0017] Furthermore, the present invention relates to a cured molded product (hereinafter, sometimes simply referred to as a "cured product") obtained by reacting, molding and curing the above-mentioned vinyl resin composition. Effect of the Invention
[0018] The vinyl resin composition of the present invention has excellent solvent solubility and is suitable for use in lamination, molding, casting, adhesion, etc., and for use in cured products thereof. Furthermore, the cured products have excellent heat resistance, thermal decomposition stability, thermal conductivity, low dielectric constant, low dielectric tangent, and flame retardancy, and are therefore suitable for use in sealing electric and electronic components, as circuit board materials, etc. [Brief description of the drawings]
[0019] [Figure 1] 1 is a GPC chart of vinyl resin A obtained in Synthesis Example 1. [Diagram 2] 1 is a GPC chart of vinyl resin B obtained in Synthesis Example 2. [Diagram 3] 1 is a GPC chart of vinyl resin C obtained in Synthesis Example 3. [Figure 4] 1 is an FD-MS spectrum of vinyl resin C obtained in Synthesis Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The present invention will be described in detail below.
[0021] The layered clay mineral as an additive used in the vinyl resin composition of the present invention is also called a tabular particle, and specifically includes smectite minerals such as talc, kaolin, mica, montmorillonite, beidellite, hectorite, saponite, nontronite, and stevensite, layered sodium silicate such as vermiculite, bentonite, kanemite, kenyanite, and makanite, mica clay minerals such as Na-type tetrasilicic fluorine mica, Li-type tetrasilicic fluorine mica, Na-type fluorine taeniolite, and Li-type fluorine taeniolite; and the like. These may be obtained from natural minerals or may be chemically synthesized. Furthermore, the layered clay mineral may be surface-modified (surface-treated) with an ammonium salt or the like. In particular, from the viewpoint of good thermal conductivity, it is preferable to use a silicate compound containing magnesium, more preferably talc or mica, and even more preferably talc.
[0022] The layered clay mineral is contained in an amount of 1 to 20 parts by weight relative to 100 parts by weight of the total amount of the resin components of the vinyl resin composition. It is preferably contained in an amount of 5 to 15 parts by weight. If the amount of the layered clay mineral in the vinyl resin composition is too small, the above-mentioned thermal conductivity may not be fully exhibited. On the other hand, if the content of the layered clay mineral is greater than this, the fluidity and heat resistance may decrease. In addition, when a highly thermally conductive inorganic filler such as alumina is contained, if the amount of the layered clay mineral is large, the content of the highly thermally conductive inorganic filler may not be sufficient, and the overall thermal conductivity may decrease. Here, the resin component refers to the vinyl resin described later and the radical polymerization initiator and modifier contained as necessary.
[0023] The vinyl resin used in the vinyl resin composition of the present invention is crystalline at room temperature, and has a melting point in the range of 90 to 200°C, preferably 110 to 180°C. The melting point is the endothermic peak temperature associated with the melting of crystals in differential scanning calorimetry. A vinyl resin having a melting point higher than 200°C has high crystallinity and tends to have reduced solvent solubility and melt-kneadability, while a cured product using a vinyl resin having a melting point lower than 90°C tends not to have improved thermal conductivity.
[0024] The vinyl resin used in the present invention preferably has a vinyl equivalent in the range of 150 to 1000 g / eq. More preferably, it is in the range of 200 to 500 g / eq. If it is greater than this range, the reactivity tends to be low, and components that remain unreacted during curing tend to be generated, leading to a decrease in heat resistance and reliability. If it is less than this range, the solvent solubility and melt-kneadability tend to decrease, and the cured product tends to become hard and brittle, leading to a decrease in film properties.
[0025] The vinyl resin used in the present invention preferably has a hydroxyl equivalent of 5000 g / eq or more with respect to the polar groups, and a total chlorine content of 2000 ppm or less. The vinyl resin used in the present invention can be obtained by reacting the hydroxyl group of a hydroxyl resin with an aromatic vinylating agent such as chloromethylstyrene. If there are many unreacted hydroxyl groups of the hydroxyl resin remaining and the hydroxyl group equivalent is less than 5000 g / eq, the curing tends to be insufficient, and the thermal conductivity and heat resistance tend to decrease. In addition, since the hydroxyl group is a polar group, the remaining hydroxyl group tends to inhibit the reduction of the dielectric constant and the dielectric loss tangent. The hydroxyl group equivalent is more preferably 8,000 g / eq or more, and even more preferably 10,000 g / eq or more.
[0026] On the other hand, the chlorine components include those derived from chloromethylstyrene and those derived from crosslinking agents in the raw materials for the production of hydroxy resins. These are difficult to remove when the vinyl resin has low solvent solubility. If the chlorine components remain at more than 2000 ppm, they tend to inhibit the reduction of the dielectric constant and dielectric loss tangent, and inhibit the curing reaction, thereby decreasing the thermal conductivity and heat resistance. The total chlorine content is more preferably 1000 ppm or less, and even more preferably 800 ppm or less.
[0027] The vinyl resin used in the present invention can be suitably obtained by reacting a hydroxy resin (hydroxy compound) with an aromatic vinylating agent. Although not limited thereto, suitable examples include vinyl resins having structures represented by the following formulas (1) to (3). The structures of the following formulas (1) to (3) are structural skeletons that can be expected to have thermal conductivity capable of suppressing intramolecular and intermolecular molecular mobility, and have good solvent solubility and melt-kneadability, so that a uniform cured product can be molded and thermal conductivity can be expressed, and are therefore preferred embodiments of vinyl resins that achieve the object of the present invention.
[0028] <Vinyl resin of formula (1)> The vinyl resin represented by the above formula (1) can be obtained by reacting the hydroxy resin (hydroxy compound) represented by the general formula (4) with chloromethylstyrene. This reaction can be carried out in the same manner as the well-known vinylation reaction. [ka] R in Equation (4) 1 ~R 6 is the same as equation (1).
[0029] In formula (1) and formula (4), R 1 ~R 6 are each independently a hydrogen atom or a monovalent hydrocarbon group having 1 to 6 carbon atoms. From the viewpoint of solvent solubility, an alkyl group is preferred, and from the viewpoint of heat resistance and high thermal conductivity, an aromatic group is preferred. With an alkyl group having more than 6 carbon atoms, it becomes difficult to suppress molecular motion, and there is a concern that compatibility may decrease. Furthermore, a bulky structure with large steric hindrance may increase crystallinity, which may decrease solvent solubility. A more preferred structure is a methyl group or a phenyl group. In formula (1) and formula (4), R 1 ~R 6 may be a mixture of different structures.
[0030] The substitution position of the vinyl benzyl ether in the vinyl resin of formula (1) is not particularly limited, but from the viewpoint of thermal conductivity and heat resistance, it is preferably the para position with respect to the methine group connecting the three aromatic rings. In particular, it is more preferable that all of the three vinyl benzyl ethers are at the para position.
[0031] The number average molecular weight (Mn) of the vinyl resin of formula (1) is preferably 2000 or less, more preferably 1500 or less. The vinyl resin may contain a multi-branched body represented by the following general formula (5). In formula (5), t is the number of repetitions (number average) and is a number from 0 to 20. The vinyl resin is preferably a mixture of components having different t values. From the viewpoint of thermal conductivity, the content of t=0 body is preferably 50 weight % (wt%) or more, more preferably 80 wt% or more. [ka]
[0032] The trifunctional hydroxy compound of formula (4) has a hydroxyl group equivalent of preferably 90 to 350 g / eq, more preferably 100 to 200 g / eq. The trifunctional hydroxy compound of formula (4) can be produced by a general method, for example, by polycondensation of a monohydric phenol compound and an aromatic aldehyde.
[0033] Examples of the monohydric phenol compound include monoalkylphenols such as phenol, o-cresol, m-cresol, p-cresol, o-ethylphenol, m-ethylphenol, p-ethylphenol, p-octylphenol, pt-butylphenol, o-cyclohexylphenol, m-cyclohexylphenol, and p-cyclohexylphenol; dialkylphenols such as 2,5-xylenol, 3,5-xylenol, 3,4-xylenol, 2,4-xylenol, and 2,6-xylenol; trialkylphenols such as 2,3,5-trimethylphenol and 2,3,6-trimethylphenol; and hydroxybiphenyls such as 2-phenylphenol, 4-phenylphenol, 3-benzyl-1,1'-biphenyl-2-ol, 3-benzyl-1,1'-biphenyl-4-ol, 3-phenylphenol, and 2,6-diphenylphenol. In terms of solvent solubility, reactivity, and supplyability, 2,5-xylenol, 2,6-xylenol, and 2-phenylphenol are particularly preferred. These phenolic compounds can be used alone or in combination of two or more kinds.
[0034] Examples of aromatic aldehydes include hydroxybenzaldehydes such as 2-hydroxybenzaldehyde, 3-hydroxybenzaldehyde, 4-hydroxybenzaldehyde, 4-hydroxy-3-methylbenzaldehyde, 4-hydroxy-3,5-dimethylbenzaldehyde, 4-hydroxy-2,5-dimethylbenzaldehyde, and 3,5-diethyl-4-hydroxybenzaldehyde. From the viewpoints of heat resistance and thermal conductivity, 4-hydroxybenzaldehyde is preferred.
[0035] The polycondensation of the phenol compound and the aromatic aldehyde may be carried out using an acid catalyst, such as acetic acid, oxalic acid, sulfuric acid, hydrochloric acid, phenolsulfonic acid, paratoluenesulfonic acid, zinc acetate, manganese acetate, etc. These acid catalysts may be used alone or in combination of two or more. Among these acid catalysts, sulfuric acid and paratoluenesulfonic acid are preferred because of their excellent activity. The acid catalyst may be added before or during the reaction.
[0036] The polycondensation of the phenol compound and the aromatic aldehyde may be carried out in the presence of a solvent, if necessary, to obtain a polycondensation product. Examples of the solvent include monoalcohols such as methanol, ethanol, and propanol; polyols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, trimethylene glycol, diethylene glycol, polyethylene glycol, and glycerin; glycol ethers such as 2-ethoxyethanol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, ethylene glycol monopentyl ether, ethylene glycol dimethyl ether, ethylene glycol ethyl methyl ether, and ethylene glycol monophenyl ether; cyclic ethers such as 1,3-dioxane, 1,4-dioxane, and tetrahydrofuran; glycol esters such as ethylene glycol acetate; and ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone. These solvents can be used alone or in combination of two or more. Among these solvents, 2-ethoxyethanol is preferred because it has excellent solubility for the resulting compound.
[0037] The reaction temperature during polycondensation of the phenol compound and the aromatic aldehyde is preferably in the range of 20 to 140°C, more preferably in the range of 80 to 110°C.
[0038] The charging ratio of the phenol compound / aromatic aldehyde is preferably in the range of 1 / 0.1 to 1 / 0.5 in terms of molar ratio, and more preferably in the range of 1 / 0.3 to 1 / 0.5, since the phenol compound after the reaction can be easily removed by reprecipitation or the like.
[0039] The vinyl resin of formula (1) can be suitably obtained by reacting a trifunctional hydroxy compound with an aromatic vinylizing agent. For example, but not limited to, the vinyl resin of the present invention suitable for use in the present invention represented by formula (1) can be obtained by reacting a trifunctional hydroxy compound represented by formula (4) with chloromethylstyrene. This reaction can be carried out in the same manner as in the well-known vinylization reaction.
[0040] The blending ratio is preferably 0.8 to 1.2 equivalents of aromatic vinylating agent (e.g., chloromethylstyrene) per 1.0 equivalent of hydroxyl group, which is the functional group of the trifunctional hydroxy compound. However, when the reactivity of the trifunctional hydroxy compound is low, it is advisable to feed an excess amount of aromatic vinylating agent and remove it after the reaction.
[0041] As the aromatic vinylating agent, halomethylstyrene, particularly chloromethylstyrene, is preferred. Other examples include bromomethylstyrene and its isomers, and those having a substituent. Regarding the substitution position of the halomethyl compound, for example, in the case of halomethylstyrene, the 4-position is preferred, and the 4-position is preferably 60% by weight or more of the total.
[0042] The reaction between the trifunctional hydroxy compound and the aromatic vinylating agent can be carried out without a solvent or in the presence of a solvent. The aromatic vinylating agent is added to the hydroxy compound, a metal hydroxide is added, and the reaction is carried out, and the generated metal salt is removed by a method such as filtration or washing with water. Examples of the solvent include, but are not limited to, methyl ethyl ketone, benzene, toluene, xylene, methyl isobutyl ketone, diethylene glycol dimethyl ether, cyclopentanone, and cyclohexanone. From the viewpoint of reactivity, methyl ethyl ketone is preferred. Specific examples of the metal hydroxide include, but are not limited to, sodium hydroxide and potassium hydroxide.
[0043] The vinylation reaction is preferably carried out at a temperature of 90° C. or less, more preferably 70° C. or less. If the temperature is higher than this temperature, the vinyl benzyl ether group may self-polymerize due to heat, making it difficult to control the reaction. To suppress self-polymerization, a polymerization inhibitor such as quinones, nitro compounds, nitrophenols, nitroso nitrone compounds, or oxygen may be used.
[0044] The end point of the reaction can be determined by tracking the remaining amount of halomethylstyrene as an aromatic vinylating agent using various chromatograms such as GPC, and the reaction rate can be adjusted by the type and amount of metal hydroxide, the addition rate, solids concentration, etc.
[0045] <Vinyl resin of formula (2) and vinyl resin of formula (3)> As the vinyl resin used in the present invention, in addition to the vinyl resin represented by formula (1), those represented by formulas (2) and (3) are also suitable. These vinyl resins may be used in combination, and it is preferable that the vinyl resins represented by formulas (1) to (3) account for 50 wt% or more of the total resin components. More preferably, it is 70 wt% or more. If the proportion used is less than this, the effect of improving the heat resistance, thermal conductivity, etc., when the cured product is obtained may be small.
[0046] [Vinyl resin of formula (2)] In the above formula (2), n is the repeat number (number average) and is a number from 0 to 20. Usually, it is a mixture of components having different repeat numbers (n), and the average value (number average) of n is preferably in the range of 0.1 to 15, more preferably in the range of 0.5 to 10. A is independently a single bond, an oxygen atom, a sulfur atom, -SO 2It represents -, -CO-, or a divalent hydrocarbon group having 1 to 6 carbon atoms, and X independently represents a benzene ring, a naphthalene ring, or a biphenyl ring. From the viewpoint of thermal conductivity, A is preferably a single bond, and X is preferably a biphenyl ring. It is desirable that the substitution positions of the two vinylbenzyl ether groups bonded to the biphenyl structure having A include at least a 2,2' isomer. In formula (2), when A is a single bond, that is, when both ends are biphenyl rings, the substitution positions of the two vinylbenzyl ether groups bonded thereto are preferably the 4,4' and 2,2' positions, and the ratio of the biphenyl at both ends is preferably 40 to 90 mol % at the 2,2' positions relative to the total. When A is other than a single bond, that is, when both ends of the vinyl resin are other than biphenyl rings, for example, when the vinyl resin has a diphenylmethane structure, it is preferable that the substitution positions of the two vinylbenzyl ether groups bonded thereto are 30 to 100 mol % at the 4,4' positions.
[0047] The vinyl resin of formula (2) is preferably a polyfunctional vinyl resin represented by the following formula (6). [ka]
[0048] In formula (6), e and f are repeat numbers (number average) and are numbers from 0 to 20. Preferably, it is a mixture of components with different values of e and f. The ratio (molar ratio) of e / (e+f) is preferably 0.50 to 0.95, more preferably 0.70 to 0.95. If it is less than 0.50, the effects of heat resistance and high thermal conductivity tend to be small, and if it is more than 0.95, the crystallinity tends to be strong and the solvent solubility tends to decrease. The average value of e is preferably 0.1 to 10, more preferably 0.5 to 5. The average value of f is preferably 0.1 to 5, more preferably 0.1 to 2. A is the same as in the above formula (2).
[0049] The polyfunctional vinyl resin represented by the above formula (6) can be produced by reacting a polyhydric hydroxy resin represented by the formula (7) with chloromethylstyrene. [ka]
[0050] In the polyhydric hydroxyl resin of formula (7), A, e, f, and the ratio of e / (e+f) are the same as those of the polyfunctional vinyl resin of formula (6). The polyhydric hydroxyl resin of formula (6) preferably has a hydroxyl equivalent of 100 to 350 g / eq. These hydroxyl groups are partially or entirely vinylized to form the polyfunctional vinyl resin of formula (6).
[0051] The polyhydric hydroxy resin of formula (7) can be produced, without limitation, by reacting 4,4'-dihydroxybiphenyl represented by formula (8) with an aromatic crosslinking agent having a biphenyl structure represented by formula (9) and then reacting the resulting mixture with a bifunctional phenol compound represented by formula (10), as shown in formula (11) below.
[0052] [ka]
[0053] [ka] Here, Z in formula (9) represents a hydroxyl group, a halogen atom or an alkoxy group having 1 to 6 carbon atoms.
[0054] [ka] Here, A is a single bond, an oxygen atom, a sulfur atom, -SO 2 It represents -, -CO-, or a divalent hydrocarbon group having 1 to 6 carbon atoms.
[0055] [ka]
[0056] The molar ratio of 4,4'-dihydroxybiphenyl represented by formula (8) and the bifunctional phenol compound represented by formula (10) when the synthesis raw materials are charged is preferably 0.50 to 0.95, more preferably 0.70 to 0.95, for 4,4'-dihydroxybiphenyl. If the ratio of 4,4'-dihydroxybiphenyl is less than this range, the heat resistance and high thermal conductivity tend to be insufficient, and if it is more than this range, the solvent solubility tends to decrease due to strong crystallinity. Specific examples of the bifunctional phenol compound of formula (10) include 2,2'-dihydroxybiphenyl, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxydiphenyl ketone, 4,4'-dihydroxydiphenyl sulfone, 4,4'-dihydroxydiphenyl sulfide, dihydroxydiphenylmethanes, and 2,2-bis(4-hydroxyphenyl)propane. In particular, 2,2'-dihydroxybiphenyl, 4,4'-dihydroxydiphenyl ether, and dihydroxydiphenylmethanes are preferred from the viewpoint of solvent solubility. The dihydroxydiphenylmethane may be a mixture of ortho, meta, and para, but isomer ratios of 4,4'-dihydroxydiphenylmethane of 40% or less are preferred. If the amount of 4,4'-dihydroxydiphenylmethane is large, there is a concern that the crystallinity is high and the solvent solubility is reduced.
[0057] In the aromatic crosslinking agent represented by the above formula (9), Z represents a hydroxyl group, a halogen atom, or an alkoxy group having 1 to 6 carbon atoms. Specific examples of the aromatic crosslinking agent include 4,4'-bishydroxymethylbiphenyl, 4,4'-bischloromethylbiphenyl, 4,4'-bisbromomethylbiphenyl, 4,4'-bismethoxymethylbiphenyl, and 4,4'-bisethoxymethylbiphenyl. From the viewpoint of reactivity, 4,4'-bishydroxymethylbiphenyl or 4,4'-bischloromethylbiphenyl is preferred, and from the viewpoint of reducing ionic impurities, 4,4'-bishydroxymethylbiphenyl or 4,4'-bismethoxymethylbiphenyl is preferred.
[0058] The molar ratio when reacting a phenol as shown in formula (11) with an aromatic crosslinking agent is generally in the range of 0.2 to 0.7 moles of aromatic crosslinking agent per mole of phenol, more preferably in the range of 0.4 to 0.7 moles. If it is less than 0.2 moles, the ratio of n=0 in the polyhydric hydroxy resin represented by formula (2) obtained will be high, and in particular, when there is a large amount of 4,4'-dihydroxybiphenyl represented by formula (8), there is concern that the solubility will decrease, such as by exhibiting crystallinity. On the other hand, if it is more than 0.7 moles, there will be a large amount of high molecular weight components, which may make it difficult to produce stably.
[0059] The reaction between the phenol and the aromatic crosslinking agent can be carried out without a catalyst or in the presence of an acid catalyst such as an inorganic acid or an organic acid. When using 4,4'-bischloromethylbiphenyl, the reaction can be carried out without a catalyst, but in general, it is preferable to carry out the reaction in the presence of an acid catalyst in order to suppress side reactions such as the reaction of a chloromethyl group with a hydroxyl group to produce an ether bond. The acid catalyst can be appropriately selected from well-known inorganic acids and organic acids, and examples of the acid catalyst include mineral acids such as hydrochloric acid, sulfuric acid, and phosphoric acid, organic acids such as formic acid, oxalic acid, trifluoroacetic acid, p-toluenesulfonic acid, methanesulfonic acid, and trifluoromethasulfonic acid, Lewis acids such as zinc chloride, aluminum chloride, iron chloride, and boron trifluoride, and solid acids.
[0060] This reaction is usually carried out at 100 to 250° C. for 1 to 20 hours, preferably at 100 to 180° C., and more preferably at 140 to 180° C. If the reaction temperature is low, the reactivity is poor and it takes a long time, whereas if the reaction temperature is high, there is a risk of decomposition of the resin.
[0061] As a solvent for the reaction, for example, alcohols such as methanol, ethanol, propanol, butanol, ethylene glycol, methyl cellosolve, ethyl cellosolve, diethylene glycol dimethyl ether, triglyme, etc., or aromatic compounds such as benzene, toluene, chlorobenzene, dichlorobenzene, etc. are preferably used, and among these, ethyl cellosolve, diethylene glycol dimethyl ether, triglyme, etc. are particularly preferred. After the reaction is completed, the solvent may be removed from the obtained polyhydric hydroxy resin by a method such as distillation under reduced pressure, washing with water, or reprecipitation in a poor solvent, but the solvent may be left as it is and used as a raw material for the vinylization reaction.
[0062] The vinyl resin of formula (2), preferably the polyfunctional vinyl resin of formula (6), can be suitably obtained by reacting a polyhydric hydroxyl resin with an aromatic vinylizing agent. For example, the polyfunctional vinyl resin of formula (6) can be obtained by reacting a polyhydric hydroxyl resin of formula (7) with chloromethylstyrene. This reaction can be carried out in the same manner as the well-known vinylation reaction. The blending ratio of these, the type of aromatic vinylating agent, reaction conditions, confirmation of the reaction end point, and the like can be the same as in the case of obtaining the vinyl resin of the above formula (1).
[0063] [Vinyl resin of formula (3)] In the above formula (3), Y is independently a direct bond, an oxygen atom, a sulfur atom, -SO 2 -, -CO-, -COO-, -CONH-, -CH 2 - or -C(CH 3 ) 2 B is independently a benzonitrile structure or -(CH 2 ) q -, and preferably contains a benzonitrile structure in at least one molecule. More preferably, contains a benzonitrile structure and -(CH 2 ) q - structures. q is a number from 3 to 10. For high thermal conductivity, Y is a direct bond biphenyl structure, -SO 2-, -CO-, -COO- or -CONH- is preferred, and a biphenyl structure having a direct bond is more preferred, and among these, a biphenyl structure having 4,4' positions is particularly preferred. On the other hand, in terms of moldability and solvent solubility, an oxygen atom, a sulfur atom, -CH 2 -, -C(CH 3 ) 2 - is preferred. As stated "independently", the vinyl resin of formula (3) can be a mixture in which each Y has a different structure, and it is possible to adjust high thermal conductivity, moldability, and solvent solubility. p is the number of repetitions and represents a number from 0 to 15. It is preferable that it represents a number from 1 to 15. It is preferable that the mixture is made of components having different values of p. The p value (average value) is preferably 1.0 to 3.0, and more preferably 1.5 to 2.5.
[0064] The vinyl resin of formula (3) may be a mixture with a compound with p=0, and the area % (GPC area %) measured by gel permeation chromatography (p=0) is preferably 40% or less. More preferably, it is 35% or less. If the amount of p=0 is more than 40%, the crystallinity is strong, the melting point exceeds 200°C, and the solvent solubility tends to decrease. In addition, if p is greater than 15, the reactivity is low, and if unreacted components are generated during curing, the heat resistance tends to decrease.
[0065] B is a benzonitrile structure or -(CH 2 ) q Preferably, at least one molecule contains a benzonitrile structure, and more preferably at least one molecule contains a benzonitrile structure and -(CH 2 ) q- and alkyl structures represented by the formula (3). That is, as B is also "independently", the vinyl resin of formula (3) can be a mixture of structures with different B, and it is possible to adjust high thermal conductivity, moldability, and solvent solubility. B contains preferably 50 mol% or more, more preferably 70 mol% or more of a benzonitrile structure. The ratio of the benzonitrile structure to the alkyl structure is preferably less than 50 mol%, more preferably 10 mol% to 40 mol%, based on the mass of the raw material compound. If the alkyl structure is more than 50 mol%, the thermal conductivity and heat resistance of the cured product tend to decrease, and if the alkyl structure is not contained, the crystallinity tends to be strong and the solvent solubility tends to decrease.
[0066] -(CH 2 ) q In the alkyl structure represented by -, q is the number of repetitions, and is a number from 3 to 10. More preferably, it is a number from 4 to 8. If it is less than 3, the flexibility and the crystallinity relaxation effect tend to be low. If it is more than 10, the thermal conductivity and heat resistance of the cured product tend to be significantly reduced.
[0067] Specifically, a preferred example of the vinyl resin is represented by the following formula (12). [ka] (wherein g and h each independently represent a number from 1 to 15, and q represents a number from 3 to 10.)
[0068] The vinyl resin of formula (3) can be conveniently obtained by reacting a hydroxy resin with an aromatic vinylating agent. For example, the vinyl resin of the present invention represented by the above formula (3) can be obtained by reacting a hydroxy resin represented by general formula (13) with chloromethylstyrene. This reaction can be carried out in the same manner as the well-known vinylation reaction. The blending ratio of these, the type of aromatic vinylating agent, reaction conditions, confirmation of the reaction end point, and the like can be the same as in the case of obtaining the vinyl resin of the above formula (1). [ka] (Y is independently a direct bond, an oxygen atom, a sulfur atom, -SO 2 -, -CO-, -COO-, -CONH-, -CH 2 - or -C(CH 3 ) 2 B is independently a benzonitrile structure or -(CH 2 ) q -, and preferably, at least one of them contains a benzonitrile structure. More preferably, at least one of them contains a benzonitrile structure and -(CH 2 ) q p and q each independently represent a number from 0 to 15, and q represents a number from 3 to 10.
[0069] The hydroxy resin represented by formula (13) (including the case where it is a mixture with a compound where p=0) has a hydroxyl equivalent (g / eq) of preferably 150 to 300, more preferably 200 to 270. The number average molecular weight (Mn) is preferably 350 to 800, more preferably 450 to 600. p has the same meaning as p in the vinyl resin of formula (3), is the number of repetitions, and is a number from 0 to 15. It is preferably a number from 1 to 15. It is preferable that the compound is a mixture of components having different values of p. The value of p (average value) is preferably 1.0 to 3.0, and more preferably 1.5 to 2.5.
[0070] The hydroxy resin (phenolic compound) represented by formula (13) may be produced by any method as long as it has a predetermined structure. It can be suitably obtained by reacting a benzonitrile compound, a dihalogen alkyl compound, and a dihydroxy compound having a Y group in the presence of a basic catalyst. In this case, examples of the benzonitrile compound include 2,4-dichlorobenzonitrile, 2,5-dichlorobenzonitrile, 2,6-dichlorobenzonitrile, 3,5-dichlorobenzonitrile, 2,4-dibromobenzonitrile, 2,5-dibromobenzonitrile, 2,6-dibromobenzonitrile, and 3,5-dibromobenzonitrile. Examples of the dihalogen alkyl compound include 1,3-dibromopropane, 1,4-dibromobutane, 1,5-dibromopentane, and 1,6-dibromohexane. Examples of the dihydroxy compound having a Y group include 4,4'-dihydroxybiphenyl, 4,4'-dihydroxydiphenyl ether, 4,4'-dihydroxydiphenyl sulfide, 4,4'-dihydroxydiphenyl sulfone, 4,4'-dihydroxybenzophenone, bisphenol A, and bisphenol F. For more detailed specific conditions regarding the production method of hydroxy resins (phenolic compounds), see, for example, WO2021 / 201046.
[0071] The vinyl resin used in the present invention can be cured by itself, but it is also suitable to use it as a vinyl resin composition containing various other additives in addition to the layered clay minerals such as talc and mica. As one of the other additives, a radical polymerization initiator such as an azo compound or an organic peroxide can be added to accelerate curing. The radical polymerization initiator may be added in an amount of, for example, 0.01 to 10 parts by weight per 100 parts by weight of the vinyl resin.
[0072] The vinyl resin composition of the present invention contains a vinyl resin and a layered clay mineral as an additive as essential components, but can also contain other vinyl compounds and other thermosetting resins, such as epoxy resins, oxetane resins, maleimide resins, acrylate resins, polyester resins, polyurethane resins, polyphenylene ether resins, and benzoxazine resins.
[0073] In order to increase the thermal conductivity, inorganic fillers other than the layered clay minerals, such as glass cloth, carbon fiber, alumina, and boron nitride, may be added.
[0074] For the purpose of imparting higher thermal conductivity, inorganic fillers with higher thermal conductivity are preferred. Thermal conductivity is preferably 20 W / m·K or more, more preferably 30 W / m·K or more, and even more preferably 50 W / m·K or more. At least a part of the inorganic filler, preferably 50 wt% or more, has a thermal conductivity of 20 W / m·K or more. The average thermal conductivity of the inorganic filler as a whole increases in the order of 20 W / m·K or more, 30 W / m·K or more, and 50 W / m·K or more.
[0075] Examples of inorganic fillers having such thermal conductivity include inorganic powder fillers such as boron nitride, aluminum nitride, silicon nitride, silicon carbide, titanium nitride, zinc oxide, tungsten carbide, alumina, and magnesium oxide. The content of the inorganic filler in the vinyl resin composition of the present invention is preferably 70% by weight or more, and more preferably 80% by weight or more, when used as a semiconductor encapsulant. The content of the inorganic filler in the vinyl resin composition of the present invention is preferably 20 to 90% by weight, and more preferably 40 to 60% by weight, when used as a heat dissipation substrate, because fluidity is required.
[0076] In order to improve the adhesive strength and the handling of the composition, various other additives may be used, such as silane coupling agents, antifoaming agents, internal mold release agents, flow control agents, etc. Furthermore, various known additives such as colorants, flame retardants, thixotropy agents, etc. may be used within the scope of the object of the present invention.
[0077] The vinyl resin composition of the present invention can be dissolved in a solvent such as toluene, xylene, acetone, methyl ethyl ketone, methyl isobutyl ketone, or cyclohexanone, impregnated into a substrate such as glass fiber, carbon fiber, polyester fiber, polyamide fiber, alumina fiber, or paper, and heated and dried to obtain a prepreg. The prepreg can then be hot-press molded to obtain a cured product.
[0078] In some cases, the vinyl resin composition of the present invention can be applied to a sheet-like material such as copper foil, stainless steel foil, polyimide film, or polyester film to form a laminate, and the resin sheet obtained by heating and drying can be subjected to hot press molding to obtain a cured product.
[0079] The vinyl resin composition of the present invention provides a cured product with high thermal conductivity, i.e., is suitable for applications that provide a cured product with high thermal conductivity. Here, the thermal conductivity of the cured product of the vinyl resin composition of the present invention is preferably 8 W / m·K or more, and more preferably 10 W / m·K or more, when it contains an inorganic filler. When it does not contain an inorganic filler, it is preferably 0.25 W / m·K or more, and more preferably 0.30 W / m·K or more. EXAMPLES
[0080] The present invention will be specifically described below with reference to examples and comparative examples. However, the present invention is not limited to these. Unless otherwise specified, "parts" refers to parts by weight, and "%" refers to % by weight. In addition, the measurement methods were each as follows.
[0081] 1) OH equivalent (hydroxyl group equivalent) Using a potentiometric titrator, acetylation was carried out with 1.5 mol / L acetyl chloride in 1,4-dioxane as a solvent, and the excess acetyl chloride was decomposed with water and titrated with 0.5 mol / L potassium hydroxide.
[0082] 2) Vinyl equivalent The sample was reacted with Wiess solution (iodine monochloride solution) and left in the dark, after which the excess iodine chloride was reduced to iodine, and the iodine content was titrated with sodium thiosulfate to calculate the iodine value, which was converted to vinyl equivalent.
[0083] 3) Total chlorine 1.0 g of sample was dissolved in 25 ml of butyl carbitol, 25 ml of 1N-KOH propylene glycol solution was added, and the mixture was heated under reflux for 10 minutes, cooled to room temperature, and 100 ml of 80% acetone water was added. 0.002N-AgNO3 It was measured by potentiometric titration in aqueous solution.
[0084] 4) GPC measurement The main body (Tosoh Corporation, HLC-8220GPC) was equipped with four columns (Tosoh Corporation, TSKgel SuperMultiporeHZ-N) in series, and the column temperature was set to 40°C. Tetrahydrofuran (THF) was used as the eluent at a flow rate of 0.35mL / min, and a differential refractive index detector was used as the detector. 0.1g of sample was dissolved in 10mL of THF and filtered through a microfilter, and 50μL of the sample was used. Data was processed using Tosoh Corporation's GPC-8020 model II version 6.00.
[0085] 5) Melting point, heat of fusion (DSC method) The measurements were performed using a Hitachi High-Tech Science DSC7020 differential scanning calorimeter, using a precisely weighed sample of about 10 mg, under nitrogen gas flow and at a heating rate of 10° C. / min.
[0086] 6) Solvent solubility (precipitation temperature) 2g of resin and 1g of methyl ethyl ketone were weighed and placed in a sample bottle, and after heating and dissolving, the temperature was gradually lowered in a thermostatic bath and the temperature in the bath at which the resin precipitated was measured. The higher the precipitation temperature (℃), the poorer the solvent solubility.
[0087] 7) Glass transition temperature (Tg) Tg was measured at a heating rate of 10° C. / min using a thermomechanical measurement device (EXSTAR TMA / 7100 manufactured by Hitachi High-Tech Science Corporation).
[0088] 8) 5% weight loss temperature (Td5), residual coal rate Using a thermogravimetric / differential thermal analyzer (Hitachi High-Tech Science EXSTAR TG / DTA7300), the 5% weight loss temperature (Td5) was measured under a nitrogen atmosphere at a heating rate of 10°C / min. The weight loss at 700°C was also measured and calculated as the residual carbon ratio.
[0089] 9) Thermal conductivity The thermal conductivity was measured by the unsteady hot wire method using a NETZSCH LFA447 thermal conductivity meter.
[0090] 10) Dielectric constant and dielectric tangent Measurements were performed in accordance with JIS C 2138. The measurement frequency was 1 GHz.
[0091] Electrodesorption ionization mass spectrometry (FD-MS) The measurement was performed using a mass spectrometer JMS-T100GCV (manufactured by JEOL Ltd.) The sample was dissolved in acetone and subjected to the measurement.
[0092] (Synthesis Example 1) In a 1000 mL four-neck flask, 73.6 g (0.60 mol) of 2,5-xylenol (structural formula 14 below) [ka] p-Hydroxybenzaldehyde (Structural formula 15 below) 24.4 g (0.20 mol) [ka] The above was charged and dissolved in 200.0 g of 2-ethoxyethanol. While cooling in an ice bath, 20.0 g of sulfuric acid was added, and the mixture was then heated and stirred at 100°C for 3 hours to react. After the reaction, the resulting solution was reprecipitated with water, washed with water, filtered, and dried in vacuum to obtain 65.0 g of a trifunctional hydroxy compound with a hydroxyl group equivalent of 118 g / eq. The trifunctional hydroxy compound is represented by the formula (4), 1 ~R 4 are all methyl groups, and R 5 and R 6 is a compound containing hydrogen atoms. Next, 59.0 g (0.17 mol) of the obtained trifunctional hydroxy compound, 400 g of methyl ethyl ketone, and 91.6 g (0.60 mol) of chloromethylstyrene (Structural Formula 16 below) were placed in a 1000 ml four-neck flask. [ka] The mixture was heated to 60°C, and 33.7 g of potassium hydroxide dissolved in 101 g of methanol was added dropwise over 3 hours, followed by a reaction for another 6 hours. After the reaction was completed, the mixture was filtered, the solvent was removed by distillation, and the mixture was reprecipitated in methanol, washed with a large amount of water, and dried under reduced pressure to obtain 102.4 g of vinyl resin (vinyl resin A). The basic structure of vinyl resin A is represented by the formula (1), where R 1 ~R 4 are all methyl groups, and R 5 and R 6 was hydrogen, the vinyl equivalent was 225 g / eq, the hydroxyl equivalent was 12,000 g / eq, the total chlorine was 600 ppm, the melting point was 130°C, and the Mn was 780. The GPC chart of the obtained vinyl resin A is shown in FIG.
[0093] (Synthesis Example 2) In a 1000 ml four-neck flask, 65.3 g (0.35 mol) of 4,4'-dihydroxybiphenyl (structural formula 17 below) [ka] Diethylene glycol dimethyl ether 121.2 g, 4,4'-bis(chloromethyl)biphenyl (structural formula 18 below) 58.7 g (0.23 mol) [ka] The mixture was heated to 170°C under a nitrogen stream while stirring and reacted for 3 hours, and then 7.8 g (0.04 mol) of dihydroxydiphenylmethane (4,4'-dihydroxydiphenylmethane (structural formula 19 below): 36.2%, 2,4'-dihydroxydiphenylmethane: 46.6%, 2,2'-dihydroxydiphenylmethane: 17.2%) was added. [ka] was reacted to produce a polyhydric hydroxy resin (hydroxyl group equivalent: 129 g / eq) according to formula (7). After the reaction was completed, 50.7 g of diethylene glycol dimethyl ether was recovered, 320 g of methyl ethyl ketone and 135.5 g of chloromethylstyrene were added, and the mixture was heated to 60°C. 49.8 g of potassium hydroxide dissolved in 150 g of methanol was added dropwise over 3 hours, and the mixture was reacted for another 6 hours. After the reaction was completed, the mixture was filtered, the solvent was distilled off, and the mixture was reprecipitated with methanol, washed with a large amount of water, and dried under reduced pressure to obtain 141 g of a white solid vinyl resin according to formula (6) (i.e., formula (2)) (vinyl resin B). The vinyl equivalent of vinyl resin B was 275 g / eq, the hydroxyl equivalent was 15,000 g / eq, the total chlorine was 300 ppm, Mn was 1330, and the melting point was 145°C. The basic structure of polyhydric hydroxyl resin and vinyl resin B is as follows: In formulas (6) and (7), A is -CH 2 - group, the ratio (molar ratio) of e / (e+f) is 0.93, e is 4.2, and f is 0.3. The GPC chart of the obtained vinyl resin B is shown in FIG.
[0094] (Synthesis Example 3) 74.5 g (0.4 mol) of 4,4'-dihydroxybiphenyl and 18.4 g (0.08 mol) of 1,5-dibromopentane (structural formula 20 below) were placed in a 2 L four-necked separable flask. [ka] After dissolving in 500 g of N-methyl-2-pyrrolidone, 41.5 g of potassium carbonate was added, and the temperature was raised to 120° C. while stirring under a nitrogen stream. Then, 20.6 g (0.12 mol) of 2,6-dichlorobenzonitrile (structure 21 below) was added. [ka] The reaction mixture was heated to 145°C and reacted for 6 hours. 28.2 g of acetic acid was added to the reaction mixture to neutralize it, and then N-methyl-2-pyrrolidone was distilled off under reduced pressure. 250 mL of methyl isobutyl ketone was added to the reaction mixture to dissolve the product, and the salt formed was removed by washing with water. Then, methyl isobutyl ketone was removed by distillation under reduced pressure to obtain 72.6 g of hydroxy resin. The hydroxyl equivalent of the obtained hydroxy resin was 225 g / eq and Mn was 520. The p value (average value) was 2.3. The basic structure of the hydroxy resin is a structural unit in which Y is a direct bond and B is a benzonitrile structure in formula (13), and -(CH 2 ) q -(q=5) Next, 74.3g (0.33 mol) of the obtained hydroxy resin, 400g of methyl ethyl ketone, and 61.0g (0.40 mol) of chloromethylstyrene were added to a 1000ml four-neck flask, and the temperature was raised to 60°C. 22.4g (0.40 mol) of potassium hydroxide dissolved in 70g of methanol was added dropwise over 3 hours, and the reaction was continued for another 6 hours. After the reaction was completed, the mixture was filtered, the solvent was distilled off, and the mixture was reprecipitated with methanol, washed with a large amount of water, and dried under reduced pressure to obtain 84.3g of a vinyl resin according to formula (12) (i.e., formula (3)) (vinyl resin C). The vinyl equivalent of vinyl resin C was 341g / eq, the hydroxyl equivalent was 10000g / eq, the total chlorine was 900ppm, Mn was 710, and the melting point was 174°C. The basic structure of vinyl resin C is represented by formula (12) and formula (3), in which q is 5, g is 1 to 3, h is 1 to 3, and p value (average value) is 1.8. The GPC chart of the obtained vinyl resin C is shown in FIG. 3, and the FD-MS spectrum is shown in FIG.
[0095] (Synthesis Example 4) In a 1000ml four-neck flask, 40.8g of 4,4'-bis(chloromethyl)biphenyl, 75.5g of 4,4'-dihydroxybiphenyl, and 120g of diethylene glycol dimethyl ether were charged, and the mixture was heated to 160°C while stirring under a nitrogen stream and reacted for 10 hours. The temperature was then raised to 70°C, 280g of diethylene glycol dimethyl ether and 129.5g of chloromethylstyrene were added, and the reaction was carried out while dropping 100.0g of 48% potassium hydroxide. It was confirmed by gas chromatography that there was no remaining chloromethylstyrene, and the solvent was recovered under reduced pressure. The obtained resin was dissolved in toluene, neutralized, and washed with water to obtain a vinyl resin (vinyl resin D). The vinyl equivalent of the obtained vinyl resin D was 256g / eq, the hydroxyl equivalent was 1500g / eq, the total chlorine was 1270ppm, Mn was 1100, and the melting point was 210°C. The relatively high melting point of vinyl resin D is presumed to be due to the following. That is, since dihydroxydiphenylmethane is not used as a raw material, the content of biphenyl components is high compared to Synthesis Example 2, and the biphenyl structure suppresses molecular motion, resulting in a high melting point of the resulting hydroxy resin. As a result, the solubility of the hydroxy resin in solvents is relatively low, and therefore, in the subsequent reaction with chloromethylstyrene, many unreacted hydroxyl groups (polar groups having hydrogen bonding properties) remain, and at the same time, flexible vinylbenzyl ether groups are reduced.
[0096] (Synthesis Example 5) In a 1000ml 4-neck flask, 50.0g of dihydroxydiphenylmethane (4,4'-dihydroxydiphenylmethane: 36.2%, 2,4'-dihydroxydiphenylmethane: 46.6%, 2,2'-dihydroxydiphenylmethane: 17.2%), 400g of methyl ethyl ketone, and 80.1g of chloromethylstyrene were added, heated to 60℃, and 29.5g of potassium hydroxide dissolved in 88g of methanol was added dropwise over 3 hours, and the reaction was continued for another 6 hours. After the reaction was completed, the mixture was filtered, the solvent was distilled off, and the mixture was reprecipitated with methanol, washed with a large amount of water, and dried under reduced pressure to obtain 95.4g of vinyl resin (vinyl resin E). The vinyl equivalent of vinyl resin E was 217g / eq, the hydroxyl equivalent was 17000g / eq, the total chlorine was 400ppm, Mn was 440, and the melting point was 80℃. The relatively low melting point of vinyl resin E is presumed to be due to the following: Unlike Synthesis Example 4, only dihydroxydiphenylmethane is used as a raw material and reacted with chloromethylstyrene, and therefore, compared to Synthesis Example 2, it is presumed that the melting point of the resulting hydroxy resin is lower due to the absence of a biphenyl component.
[0097] Examples 1 to 5, Comparative Examples 1 to 4 Vinyl resins A to E obtained in Synthesis Examples 1 to 5 were used as vinyl resins, and talc (additive A, average particle size 10 to 15 μm, Fujifilm Wako Pure Chemical Industries, Ltd.) was used as an additive, Perbutyl P (NOF Corporation, an organic peroxide) was used as a curing accelerator, Adeka STAB AO-60 (ADEKA Corporation, Ltd.) was used as an antioxidant, spherical alumina (Denka, DAW-10, average particle size 12.2 μm) was used as inorganic filler A, and spherical silica (Denka, FB-8S) was used as inorganic filler B. These were mixed in the blending ratios shown in Table 1 and dissolved in a solvent to form a uniform composition. This composition was applied to a PET film and dried at 130°C for 5 minutes to obtain a resin composition (resin sheet). The composition removed from the PET film was sandwiched between mirror plates and cured under reduced pressure at 130°C for 15 minutes and at 210°C for 80 minutes while applying a pressure of 2 MPa. The properties of the obtained cured product are shown in Table 1.
[0098] The cured products made of the vinyl resin compositions of the Examples exhibited excellent physical properties, such as high thermal conductivity, low dielectric constant and low dielectric loss tangent, as compared with the Comparative Examples. [Table 1] [Industrial Applicability]
[0099] The vinyl resin composition and the cured product of the present invention are useful as electronic materials for high-speed communication devices, as they easily dissipate heat generated from electronic components and wiring and have little signal loss.
Claims
1. A vinyl resin composition comprising a vinyl resin and an additive, the additive being a layered clay mineral, the composition containing 1 to 20 parts by weight of the layered clay mineral per 100 parts by weight of the resin component, and the vinyl resin having a melting point of 90 to 200°C.
2. 2. The vinyl resin composition of claim 1, wherein the additive is talc.
3. The vinyl resin composition according to claim 1 or 2, characterized in that the vinyl resin has a vinyl equivalent of 150 to 1000 g / eq, a hydroxyl equivalent of 5000 g / eq or more, and a total chlorine content of 2000 ppm or less.
4. The vinyl resin composition according to claim 1 or 2, wherein the vinyl resin is represented by any one or more of the following general formulas (1) to (3): 【Chemistry 1】 In formula (1), R 1 ~R 6 each independently represents a hydrogen atom or a monovalent hydrocarbon group having 1 to 6 carbon atoms. 【Chemistry 2】 In formula (2), A is independently a single bond, an oxygen atom, a sulfur atom, or -SO 2 It represents --, --CO-- or a divalent hydrocarbon group having 1 to 6 carbon atoms, X is independently a benzene ring, a naphthalene ring or a biphenyl ring, and n is a number from 0 to 20. 【Chemistry 3】 In formula (3), Y is independently a single bond, an oxygen atom, a sulfur atom, or -SO 2 -, -CO-, -COO-, -CONH-, -CH 2 - or -C(CH 3 ) 2 B is independently a benzonitrile structure or -(CH 2 ) q -, p is a number from 0 to 15, and q is a number from 3 to 10.
5. 3. The vinyl resin composition according to claim 1, further comprising 20 to 90 wt % of an inorganic filler other than layered clay minerals.
6. 3. The vinyl resin composition according to claim 1, which is a vinyl resin composition that gives a cured product having high thermal conductivity.
7. A cured product obtained by curing the vinyl resin composition according to claim 1 or 2.
Citation Information
Patent Citations
Liquid crystal epoxy monomer and liquid crystal epoxy resin
JP1997118673A
Epoxy resin composition for semiconductor sealing and semiconductor device
JP1999147936A
Insulation composition
JP1999323162A
Epoxy resin composition for sealing and semiconductor device
JP2002309067A
Wiring board
JP2009170493A